Livelihood Sensitivity Matrix: A Novel Technique for Mapping Vulnerability of Rural Households to Climate Change - Usha Das and Souvik Ghosh, (Indian Journal of Extension Education, 2018)
Almost all nations are aware of changing climatic scenario and India is not an exception and neither immunefrom the impact of climate change. The lives of inhabitants are most at risk from cyclone and flood thanfrom drought and heat wave. Poor are the worst affected. Livelihood group wise as well as climatic hazardwise vulnerability index through exposure and impact matrix was developed based on the responses ofselected households sampled for present study. To understand the livelihood group wise as well as climaticevent wise vulnerability the exposure index and impact index were derived. Crop farmers are most exposedlivelihood group followed by labourers, livestock keepers and fish farmers. Cyclone has made highestimpact on livelihoods followed by flood, drought and heat wave, respectively. The outlooks for the vulnerableregions are not good unless on-farm contingency plans, both short and long-term, are adopted.